Banana accompanying measures : supporting the sustainable adjustment of the main ACP banana-exporting countries to new trade realities (European Commission BrusselsBE, 2010)
Looks at the objectives, beneficiaries, intervention areas and the implementing modalities of the new Banana Accompanying Measures.
Keywords: BANANAS